Defining 'Resilient Design' in the Context of Consumer Products. (2nd January 2018) - Haug, Anders
Abstract: In recent decades, a widely discussed means of achieving environmental sustainability is to design more durable products, thereby reducing the need for the production of new products. In particular, the emotional perspective on product durability has received attention in recent design literature, since consumer products are often replaced long before they become physically non-functioning. The literature includes many accounts of causes of product replacement and means of making products more durable. Such classifications, however, include different sets of causes and means, making 'product durability' a concept that involves different understandings, depending on the underlying literature. Furthermore, this paper argues that only using the term 'durability' may cause certain aspects to be neglected in the effort to make consumer products longer lasting. The paper addresses these issues by defining the concept of 'resilient design', providing a detailed classification of causes of product replacement and organizing means to extend product longevity.